Activation‐Induced Cytidine Deaminase Regulates Fibroblast Growth Factor/Extracellular Signal‐Regulated Kinases Signaling to Achieve the Naïve Pluripotent State During Reprogramming. (8th May 2019) - Kumar, Ritu; Evans, Todd
Abstract: Induced pluripotent stem cells (iPSCs) derived by in vitro reprogramming of somatic cells retain the capacity to self‐renew and to differentiate into many cell types. Pluripotency encompasses multiple states, with naïve iPSCs considered as ground state, possessing high levels of self‐renewal capacity and maximum potential without lineage restriction. We showed previously that activation‐induced cytidine deaminase (AICDA) facilitates stabilization of pluripotency during reprogramming. Here, we report that Acida −/− iPSCs, even when successfully reprogrammed, fail to achieve the naïve pluripotent state and remain primed for differentiation because of a failure to suppress fibroblast growth factor (FGF)/extracellular signal‐regulated kinases (ERK) signaling. Although the mutant cells display marked genomic hypermethylation, suppression of FGF/ERK signaling by AICDA is independent of deaminase activity. Thus, our study identifies AICDA as a novel regulator of naïve pluripotency through its activity on FGF/ERK signaling.Stem Cells 2019;37:1003–1017 Abstract : Fibroblasts lacking activation‐induced cytidine deaminase (indicated as AID) can be reprogrammed to pluripotency using low levels of reprogramming factors, yet even under these conditions, they fail to achieve the naïve state and remain in a primed epiblast stem cell‐like state. The primary defect appears to be excessive extracellular signal‐regulated kinases signaling, which can be reversed by forced expression of AID.